PENGARUH STRUCTURE YANG DIBERIKAN DOSEN TERHADAP COMPETENCE NEED SATISFACTION PADA MAHASISWA PSIKOLOGI UNIVERSITAS NEGERI X YANG SEDANG MENYUSUN SKRIPSI - Dita pratiwi; Putri Sukma Deri; Mario Pratama; Izzanil Hidayati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Writing an undergraduate thesis is a complex academic process that often leads students to doubt their own abilities. This condition indicates that competence need satisfaction (CNS), as explained in Self-Determination Theory, has not been optimally fulfilled. This study aimed to examine the effect of structure provided by supervisors on the competence need satisfaction of Psychology students at University X who were completing their undergraduate theses. This study employed a quantitative method with a correlational design involving 253 Psychology students who were writing their undergraduate theses, selected using a convenience sampling technique. The research instruments were the modified TASCQ–Short Form and the modified Basic Psychological Need Satisfaction Scale (BPNSS), with reliability coefficients of 0.882 and 0.727, respectively. The data were analyzed using simple linear regression analysis. The results showed that the structure provided by supervisors had a positive and significant effect on students' competence need satisfaction (R = 0.307; R² = 0.094; p < .05). The findings indicate that structure contributed 9.4% to students' competence need satisfaction, while the remaining 90.6% was explained by other factors beyond the scope of this study. These findings highlight the important role of supervisors' structure in supporting students' competence need satisfaction throughout the undergraduate thesis writing process.